Multistep Chemical Processing of Crickets Leading to the Extraction of Chitosan Used for Synthesis of Polymer Drug Carriers - Głąb, Magdalena; Kudłacik-Kramarczyk, Sonia; Drabczyk, Anna; Guigou, Martin Duarte; Sobczak-Kupiec, Agnieszka; Mierzwiński, Dariusz; Gajda, Paweł; Walter, Janusz; Tyliszczak, Bożena (Materials, 2021)
Chitosan belongs to the group of biopolymers with increasing range of potential applications therefore searching for new raw materials as well as new techniques of obtaining of this polysaccharide are currently a subject of interest of many scientists. Presented manuscript describes preparation of chitosan from crickets. Obtainment of final product required a number of processes aimed at removal of undesirable substances such as waxes, mineral salts, proteins or pigments from above-mentioned insects. Chemical structure of fractions obtained after each step was compared with the structure of commercial chitosan by means of techniques such as X-ray diffraction and FT-IR spectroscopy. Final product was subsequently used for preparation of polymer capsules that were modified with active substance characterized by antibacterial and anticancer activity—nisin. Next, sorption capacity of obtained materials was evaluated as well as a release profile of active substance in different environments. Based on the conducted research it can be concluded that crickets constitute an alternative for shellfish and other conventional sources of chitosan. Furthermore, obtained capsules on the basis of such prepared chitosan can be considered as drug delivery systems which efficiency of release of active substance is bigger in alkaline environments.